THE EFFECT OF HIGH-INTENSITY FOCUSED ELECTRO-MAGNETIC (HIFEM) THERAPY ON URINARY INCONTINENCE - Daryanto, Besut; Kustono, Andri; Negara, Edvin Prawira (MNJ (Malang Neurology Journal), 2024)
Introduction: Urinary incontinence (UI) is an involuntary leakage of urine, regardless of the amount or frequency, which alters physical, emotional, and social well-being and quality of life. The therapy currently being studied is magnetic stimulation (MS) has been used to stimulate the pelvic floor muscles. It is based on Faraday's law of magnetic induction, where a changing magnetic field over time induces electrical activity that depolarizes nerves and causes contraction of the pelvic floor muscles. However, the research on the effect of High-Intensity Focused Electromagnetic is still minimal, especially in Indonesia, so its effectiveness in overcoming UI in Indonesia is still doubtful. Method: This study used a prospective cohort design where patients were followed for one month. Patients were followed from when they were first diagnosed until the therapy was completed and evaluated. The variables in this study were as follows: pre and post International Prostate Symptom Score (IPSS), Overactive Bladder Syndrome Score (OABSS), Barhal index, and progress of patient complaints from the first therapy. Result: This research was conducted for 6 sessions, and significant results were obtained in sessions 1, 4, 5, and 6. From this data, we conclude that the HIFEM therapy had a significant effect from session 4. Furthermore, we found a significant therapeutic effect between sessions 4 and 6, but not between sessions 4 and 5. There was also a significant therapeutic effect between sessions 5 and 6. Conclusion: HIFEM can improve incontinence and OAB complaints. HIFEM works to strengthen the pelvic floor muscles.